Effect of botulinum toxin type A on non-motor symptoms and quality of life in Meige syndrome - Zheng, Heqing; Wu, Lanxiang; Tian, Sheng; Liu, Mingxu; Zhan, Qingqing; Yu, Xinping; Xie, Yonggang; Zhong, Xianhui; Wu, Wei (Frontiers in Neurology, 2023)
Background It has been shown in previous studies that botulinum toxin type A (BTX-A) can effectively relieve the motor symptoms of Meige syndrome. However, its effect on non-motor symptoms (NMS) and quality of life (QoL) has not been comprehensively studied. This study aimed to explore the effects of BTX-A on NMS and QoL and to clarify the relationship between changes in motor symptoms, NMS, and QoL after BTX-A. Methods Seventy-five patients were recruited for the study. All patients were assessed by a series of clinical assessments before, one, and 3 months after BTX-A treatment. Dystonic symptoms, psychiatric disturbances, sleep disorders, and QoL were evaluated. Results After 1 and 3 months of BTX-A treatment, the scores of motor symptoms, anxiety, and depression were significantly decreased (P < 0.05). Except for general health, the scores of the other 36-item short-form health survey QoL subitems were significantly improved after BTX-A (P < 0.05). After 1 month of treatment, the changes in anxiety and depression were not correlated with changes in motor symptoms (P > 0.05). Still, they were negatively correlated with changes in physical functioning, role-physical and mental component summary QoL (P < 0.05). Conclusions BTX-A effectively improved motor symptoms, anxiety, depression, and QoL. Anxiety and depression improvement did not correlate with motor symptom changes after BTX-A, and QoL improvements were strongly associated with psychiatric disturbances.